DESIGNING A TEACHING MODEL FOR GREEN EDUCATION BASED ON QUR’ANIC SEMITIC RHETORIC - Asnawi, Aqdi Rofiq (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
The global ecological crisis demands innovative approaches to education that are both ethically grounded and culturally authentic. Within the Islamic tradition, the Qur’an provides not only theological guidance but also rhetorical structures that can be translated into pedagogical strategies. This paper proposes the design of a teaching model for green education inspired by Qur’anic Semitic Rhetoric. While existing studies on Islamic environmental education have largely emphasized values, ethics, and jurisprudence, few have addressed how the Qur’an’s rhetorical architecture—such as concentric, parallel, and mirror structures—can be systematically transformed into classroom pedagogy. Through textual analysis of selected ecological verses, this study shows how concentric structures highlight stewardship (khilāfah) as the central axis of ecological ethics, parallel structures foster critical awareness through contrasts between corruption and care, and mirror structures reinforce reflective learning by returning students to a core principle of responsibility. These rhetorical strategies were developed into a Qur’anic Rhetorical Teaching Model for Green Education, complete with lesson designs, classroom activities, and pedagogical outcomes. The model demonstrates that Qur’anic rhetoric can deepen comprehension, strengthen memory, and encourage behavioral transformation, thereby bridging the gap between eco-theological theory and applied pedagogy. This contribution not only advances Islamic pedagogy and environmental education but also offers a practical framework adaptable to schools, pesantren, and higher education institutions, where ecological consciousness can be nurtured as both a moral and spiritual imperative.